Variability and inheritance of peach SSR sequences in almond genotypes - Sánchez-Pérez R.; Dicenta F.; Martínez-Gómez P.; Ruiz C.; Ballester J.; Arús P. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
Variability and inheritance of six peach [Prunus persica (L.) Batsch] SSR (simple-sequence repeat) markers was studied in 21 almond [P. dulcis (Mill.) D.A. Webb] cultivars and in a progeny of 180 descendants from the cross between the French cultivar 'R1000' and the Spanish cultivar 'Desmayo Largueta'. The results showed the molecular identification of the 21 cultivars using the six SSR polymorphic sequences. The number of alleles revealed by the SSR analysis ranged from 4 to 13, with a high level of heterozygosity. A codominant segregation of the SSRs was observed in this progeny. These results establish the value of SSR markers for distinguishing different genetic lineages and characterize the extensive gene pool available for almond breeding programs. The application of these SSR sequences in the development of markers associated with genes or QTLs involved in the inheritance of agronomic traits in almond is also discussed.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)